LES LOGIQUES TRADITIONNELLES D’EXPLOITATION DES TERRES EN MILIEU RURAL IVOIRIEN : L’EXEMPLE DU SYSTÈME « ABOUYA-ACHI » DANS LA SOCIÉTÉ AKYÉ - Simon, Affessi Adon (European Scientific Journal, ESJ, 2015)
This study would on the one hand analyze the different transactions that go around the land in rural akye and on the other describe the relations of power in the land access by the system "abouya-achi" and the consequences that such a practice can generate.For the akye peasant, the administration of his land was focused on traditional values. Because of its inalienable characteristic, akye land could only be acquired by loan, inheritance and donation. Also, with the revitalization of akye society, the commercialization of land and the "abouya-achi" system appear as the last means of access to the land. The "abouya-achi" system which means in akye "divide to eat" creates relations of dependency (kpécin) and of '' master '' (biabi).Without a legal basis, without a serious contract clause, this form of exploitation of the land is the result of latent land conflict with serious consequences like those we have seen in Côte d’Ivoire.